Prodigious plant methylomes. Issue 1 (December 2016) - Gehring, Mary
Abstract Schmitz and colleagues recently investigated DNA methylation patterns in diverse flowering plant species, finding substantial variation in the extent and distribution of methylation in angiosperms. Please see related Research article:http://www.doi.org/10.1186/s13059-016-1059-0